(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2023)
This paper provides a comprehensive survey of the Iberian inscriptions coming from the territory of the Oretani that are related to burials or funerary contexts. We then specifically focus on two stones with Iberian inscriptions from the towns of Iliturgi and Castulo. Both can be interpreted as funerary steles and, accordingly, we must assume that the area of distribution of Iberian funerary epigraphy reaches further south than had previously thought.